Kochia (Kochia scoparia) Emergence Profiles and Seed Persistence across the Central Great Plains. Issue 5 (15th June 2017) - Dille, J. Anita; Stahlman, Phillip W.; Du, Juan; Geier, Patrick W.; Riffel, Jarrett D.; Currie, Randall S.; Wilson, Robert G.; Sbatella, Gustavo M.; Westra, Philip; Kniss, Andrew R.; Moechnig, Michael J.; Cole, Richard M.
Abstract : Timing of weed emergence and seed persistence in the soil influence the ability to implement timely and effective control practices. Emergence patterns and seed persistence of kochia populations were monitored in 2010 and 2011 at sites in Kansas, Colorado, Wyoming, Nebraska, and South Dakota. Weekly observations of emergence were initiated in March and continued until no new emergence occurred. Seed was harvested from each site, placed into 100-seed mesh packets, and buried at depths of 0, 2.5, and 10 cm in fall of 2010 and 2011. Packets were exhumed at 6-mo intervals over 2 yr. Viability of exhumed seeds was evaluated. Nonlinear mixed-effects Weibull models were fit to cumulative emergence (%) across growing degree days (GDD) and to viable seed (%) across burial time to describe their fixed and random effects across site-years. Final emergence densities varied among site-years and ranged from as few as 4 to almost 380, 000 seedlings m −2 . Across 11 site-years in Kansas, cumulative GDD needed for 10% emergence were 168, while across 6 site-years in Wyoming and Nebraska, only 90 GDD were needed; on the calendar, this date shifted from early to late March. The majority (>95%) of kochia seed did not persist for more than 2 yr. Remaining seed viability was generally >80% when seeds were exhumed within 6 mo after burial in March, and declined to <5% by October of the first year after burial. Burial did not appear to increase or decrease seed viability over time but placed seed in a position from which seedling emergence would not be possible. High seedling emergence that occurs very early in the spring emphasizes the need for fall or early spring PRE weed control such as tillage, herbicides, and cover crops, while continued emergence into midsummer emphasizes the need for extended periods of kochia management.